Gdxray: The Database of X-Ray Images for Nondestructive Testing - Zuccar-Parrini, I (Springer New York LLC, 2015)
In this paper, we present a new dataset consisting of 19,407 X-ray images. The images are organized in a public database called $$\mathbb {GDX}$$GDXray that can be used free of charge, but for research and educational purposes only. The database includes five groups of X-ray images: castings, welds, baggage, natural objects and settings. Each group has several series, and each series several X-ray images. Most of the series are annotated or labeled. In such cases, the coordinates of the bounding boxes of the objects of interest or the labels of the images are available in standard text files. The size of $$\mathbb {GDX}$$GDXray is 3.5 GB and it can be downloaded from our website. We believe that $$\mathbb {GDX}$$GDXray represents a relevant contribution to the X-ray testing community. On the one hand, students, researchers and engineers can use these X-ray images to develop, test and evaluate image analysis and computer vision algorithms without purchasing expensive X-ray equipment. On the other hand, these images can be used as a benchmark in order to test and compare the performance of different approaches on the same data. Moreover, the database can be used in the training programs of human inspectors. © 2015, Springer Science+Business Media New York.